Enrichment of the airway microbiome in people living with HIV with potential pathogenic bacteria despite antiretroviral therapy. (July 2020) - Rofael, Sylvia A.D.; Brown, James; Pickett, Elisha; Johnson, Margaret; Hurst, John R.; Spratt, David; Lipman, Marc; McHugh, Timothy D.
Abstract: Background: Long-term antiretroviral therapy (ART) enables people living with HIV (PLW-HIV) to be healthier and live longer; though they remain at greater risk of pneumonia and chronic lung disease than the general population. Lung microbial dysbiosis has been shown to contribute to respiratory disease. Methods: 16S-rRNA gene sequencing on the Miseq-platform and qPCR for typical respiratory pathogens were performed on sputum samples collected from 64 PLW-HIV (median blood CD4 count 676 cells/μL) and 38 HIV-negative participants. Finding: Richness and α-diversity as well as the relative-abundance (RA) of the major taxa (RA>1%) were similar between both groups. In unweighted-Unifrac ß-diversity, the samples from PLW-HIV showed greater diversity, in contrast to the HIV negative samples which clustered together. Gut bacterial taxa such as Bilophila and members of Enterobacteriaceae as well as pathogenic respiratory taxa ( Staphylococcus, Pseudomonas and Klebsiella ) were significantly more frequent in PLW-HIV and almost absent in the HIV-negative group. Carriage of these taxa was correlated with the length of time between HIV diagnosis and initiation of ART (Spearman-rho=0·279, p =0·028). Interpretation: Although the core airway microbiome was indistinguishable between PLW-HIV on effective ART and HIV-negative participants, PLW-HIV's respiratory microbiome was enriched with potential respiratory pathogens and gut bacteria. The observed differences in PLW-HIV may be due to HIV infection altering the local lung microenvironment to be more permissive to harbour pathogenic bacteria that could contribute to respiratory comorbidities. Prompt start of ART for PLW-HIV may reduce this risk.